2010
DOI: 10.1093/ndt/gfp696
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomic characterization between normal peritoneal fluid and diabetic peritoneal dialysate

Abstract: The loss of vitamin D-binding protein, haptoglobin and alpha-2-microglobulin may be due to a change in the permeability of the peritoneal membrane to middle-sized proteins or leakage from peritoneal inflammation. Lower levels of complement C4-A in dialysate may shed light on the beginning of peritoneal membrane scleroses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…The determination of DBP in peritoneal fluid could be useful to monitor vitamin D deficiency in peritoneal dialysis patients. Due to a change in the permeability of the peritoneal membrane to middle-sized proteins or leakage of DBP from peritoneal inflammation, DBP losses in the peritoneal fluid have been demonstrated by two-dimensional gel electrophoresis [48]. In the peritoneal dialysate effluents of peritoneal dialysis patients with high transporter characteristics of the peritoneal membrane, a significant higher amount of DBP has been detected in comparison with subjects with other transporter characteristics [49].…”
Section: Vitamin D Binding Protein In Ascitic Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of DBP in peritoneal fluid could be useful to monitor vitamin D deficiency in peritoneal dialysis patients. Due to a change in the permeability of the peritoneal membrane to middle-sized proteins or leakage of DBP from peritoneal inflammation, DBP losses in the peritoneal fluid have been demonstrated by two-dimensional gel electrophoresis [48]. In the peritoneal dialysate effluents of peritoneal dialysis patients with high transporter characteristics of the peritoneal membrane, a significant higher amount of DBP has been detected in comparison with subjects with other transporter characteristics [49].…”
Section: Vitamin D Binding Protein In Ascitic Fluidmentioning
confidence: 99%
“…In the peritoneal dialysate effluents of peritoneal dialysis patients with high transporter characteristics of the peritoneal membrane, a significant higher amount of DBP has been detected in comparison with subjects with other transporter characteristics [49]. Due to the loss of DBP in the ascitic fluid, a decreased serum DBP concentration could lead to alterations in the serum 25(OH)-vitamin D 3 concentration [48]. However, this statement has been criticized by another group, who showed that the peritoneal loss of DBP was not accompanied by a serum DBP deficiency due to an adapted hepatic synthesis [49].…”
Section: Vitamin D Binding Protein In Ascitic Fluidmentioning
confidence: 99%
“…An average of 200 protein spots were detected in both gels. Among these, 17 spots were found with higher levels in the peritoneal dialysate (indicated in A by arrows) and 9 spots were found with higher levels in the control samples (indicated in B by arrows) [Adapted from (Wang et al 2010)] Fig. 7.…”
Section: The Role Of Glucose In Peritoneal Dialysismentioning
confidence: 99%
“…Western blotting of the identified proteins in five individual DM samples and two individual control samples: the mean band density of five DM samples and two control samples were calculated and fold change between the two groups was calculated by dividing the mean band density of the DM samples by that of the control samples; the mean density of the control groupwas adjusted as 1, and the fold changewas put in the bracket beloweach set of bands [(A) proteins, vitamin D-binding protein, haptoglobin and α-2-microglobulin show higher expression levels in the DM samples than in the control samples; (B) proteins, complement C4-A and IGK@ protein show higher expression levels in the two control samples than in the five DM samples]. [Adapted from (Wang et al 2010)] However, the details of the pathogenic mechanism remain unclear. Protein changes between peritoneal dialysate from specific disease and normal peritoneal fluids may shed light to better understanding of the mechanism involved in peritoneal damage resulting from www.intechopen.com peritoneal dialysis.…”
Section: The Role Of Glucose In Peritoneal Dialysismentioning
confidence: 99%
See 1 more Smart Citation